Optimal and robust control : advanced topics with MATLAB́ - Fortuna, L. (Luigi), 1953-; Frasca, Mattia (Boca Raton, FL : CRC Press, 2012)
"The scope of this book is to give to people with the knowledge of the main concepts of automatic control and signals and systems analysis a self-contained resource for advanced techniques both in linear system theory and in control design. This is achieved by including selected theoretical backgrounds, many numerical exercises and MATLAB examples. In this work we offer a complete and easy-to-read handbook of advanced topics in automatic control including the LQR and the H [infinity symbol] approach. Moreover our task has been to take advanced concepts of modeling analysis and to present the essential items of the new technique of LMI in order to show how it can be considered as a unifying tool for system analysis and controller design. The robustness property of the closed control loop is the guideline of the book. The text deals with advanced automatic control techniques with particular attention to their robustness"--Preface.
Includes bibliographical references (p. 217-222) and index.
HB
Keywords: Robust control -- Mathematical models; Linear systems; Automatic control; TECHNOLOGY & ENGINEERING / Electrical; TECHNOLOGY & ENGINEERING / Electronics / Microelectronics; TECHNOLOGY & ENGINEERING / Mechanical